PENGARUH KESALAHAN PEMBERIAN OPINI AUDITOR MENGENAI GOING CONCERN PERUSAHAAN TERHADAP REPUTASI AUDITOR - Diah Agustina Prihastiwi; Yulida Army Nurcahya; Kartika Pradana Suryatimur (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this study is to analyze the relationship between disclosure of provision and contingency transactions and errors in giving auditor opinions that can predict company bankruptcy in state-owned companies. This is done considering that various strategic resources in Indonesia are managed by state-owned companies. The study found that when a company goes bankrupt, the company often has a clean audit opinion, which means everything looks good on paper. However, just because it looks good does not mean the company is actually doing well. On the other hand, if a company gets a GCO opinion, which means there is a serious problem, it is likely that they will have problems. This shows that we need to be very careful when looking at a company's financial statements and what the auditors say. Everyone involved should pay close attention and do their homework.